From Zero to Digital Hero: Dasar-Dasar Digital Marketing untuk Pemula - Bakri Bakri; Badriyah Badriyah; Retno Widowati; Mira Firlana (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
The rapid development of digital technology requires communities to possess basic digital marketing literacy and skills in order to adapt to technology-based communication and marketing patterns. The main problem faced by the target participants in this Community Service Program was the low level of understanding and basic skills in utilizing digital media, particularly YouTube and TikTok, for promotion and information dissemination. This program aimed to enhance the capacity of beginners through an applied and contextual basic digital marketing training. The method employed an educative and participatory approach through interactive lectures, discussions, and hands-on content creation practices. The results indicate an improvement in participants’ understanding of digital marketing concepts, their ability to use social media functionally, and their initial readiness to produce simple digital content. These findings confirm that a beginner-oriented training model is effective as a community empowerment instrument in the digital era. This program contributes to strengthening digital literacy and has the potential to be replicated in other communities with similar characteristics.